Effectiveness of Tai Ji Quan for Anxiety and Depression (Global Journal of Medical Research, 2015)
Tai Ji Quan is always considered to be an exercise that has the same benefit as other exercise when it is done properly. Once considered as a martial art, nowadays, people think that practising Tai Ji is one of many ways to prevent illness, and getting a better health. Some studies have proven the benefit of Tai Ji in several medical condition, however the efficacy of Tai Ji for psychiatric conditions is very limited due to the limitation of variety of studies. Some studies propose that Tai Ji might have efficacy in treating anxiety or depression, whether it is as an augmentation or a single therapy for the patients.
Keywords: Tai ji quan; anxiety; depression